A Perspective on the Transition to Plant-Based Diets: a Diet Change May Attenuate Climate Change, but Can It Also Attenuate Obesity and Chronic Disease Risk?. Issue 1 (3rd September 2019) - Magkos, Faidon; Tetens, Inge; Bügel, Susanne Gjedsted; Felby, Claus; Schacht, Simon Rønnow; Hill, James O; Ravussin, Eric; Astrup, Arne
ABSTRACT: Current dietary guidelines advocate more plant-based, sustainable diets on the basis of scientific evidence about diet–health relations but also to address environmental concerns. Here, we critically review the effects of plant-based diets on the prevalence of obesity and other health outcomes. Plant-based diets per se have limited efficacy for the prevention and treatment of obesity, but most have beneficial effects in terms of chronic disease risk. However, with the considerable possibilities of translating plant-based diets into various types of dietary patterns, our analysis suggests that potential adverse health effects should also be considered in relation to vulnerable groups of the population. A transition to more plant-based diets may exert beneficial effects on the environment, but is unlikely to affect obesity, and may also have adverse health effects if this change is made without careful consideration of the nutritional needs of the individual relative to the adequacy of the dietary intake.